FUNCTIONAL RECOVERY OF ELBOW COMPLEX IN MONTEGGIA FRACTURE-DISLOCATION - PRESENTATION OF CASE - Becheva, M. V. (International Journal of Research -GRANTHAALAYAH, 2016)
The treatment of elbow joint fractures is a serious medical and social problem due to frequent complications and impairment of the ability of self-service and performance of various household and labour activities. We needed evidence as to which exercises were appropriate in the treatment of patients with fracture elbow-Monteggia. The aim of the presented clinical case is to examine the effectiveness of the applied kinesitherapeutic methodology in Monteggia fracture-dislocation treated surgically by internal fixation. Kinesitherapy was carried out in two phases (maximally and moderately protective), and as a result of the applied means of functional recovery, there was achieved a good elbow reintegration in the motor circuit of upper limb. There was observed a small deficit in terms of flexion and extension in the right elbow joint, which should be ascribed to the lack of artromot, as well as to insufficient patient motivation. Global functions reported by MEPS were 84/100.